Effect of liquid properties (water and lime juice) on spray characteristics of deflected flat spray nozzle (AL-75) - Abd Rahman, Muhammad Faqhrurrazi (2017)
Nowadays, the application of the nozzle has been widely used in the industry. The main factor that influences the spray is pressure of the liquid and air, type of nozzle, type of spray and the viscosity of the liquid. The problem in this research is to determine minimum liquid pressure used for atomization. This study is on characteristic with different ratio of liquid properties which can affect the spray behaviour for this spray such as spray angle, spray development and velocity. The objective for this research is to get the best atomizer within 1 bar to 3 bar liquid pressure for household piping. For this study, the pressure of liquid used was 1 bar, 2 bar and 3 bar, whereas the pressure of air used was 1 bar, 3 bar and 6 bar. Another objective is to identify characteristic study of spray angle, spray development and velocity of flat fan spray nozzle by using different liquid properties. 3 different fluids were tested with deflected flat spray nozzle (AL-75); 100% water, L10W90 (consist of 10% lime and 90% water) and L30W70 (consist of 30% lime and 70% water). Final objective is to validate result for spray angle and velocity between experiment and simulation using ANSYS CFX version 15.0. Based on the obtained results, the duration of fully development for deflected flat spray nozzle (AL-75) operated at the combination of 3 bar liquid pressure with 3 bar air pressure was 24ms, compared to spray nozzle operated at the combination of 1 bar liquid pressure with 1 bar air pressure with 32ms. This is because, an increase in pressure were decreases the duration for spray pattern to be fully developed. Velocity of 100% water was the highest compared to L10W90 and L30W70. This is due to the fact that as viscosity increased, the velocity of spray decreases. Spray angle result shows that water have wider angle compared to L10W90 and L30W70. As viscosity increased, the spray angles become narrow and simultaneously reduce the spray angle.